Firing up the cold tumors by targeting Vps34. (1st January 2020) - Janji, Bassam; Hasmim, Meriem; Parpal, Santiago; Berchem, Guy; Noman, Muhammad Zaeem
ABSTRACT: Cancer immunotherapy based on anti-PD-1/PD-L1 blockade is particularly effective in responding to patients with hot tumors. These tumors are characterized by the accumulation of proinflammatory cytokines and T cell infiltration. In our recent report published in Science Advances, we demonstrate that targeting the autophagy-related protein Vps34 switched cold immune desert tumors into hot inflamed immune-infiltrated tumors and enhanced the efficacy of anti-PD-1/PD-L1. Our study provides the preclinical rationale to set up combination immunotherapy clinical trials using selective Vps34 inhibitors and immune checkpoint blockers in melanoma and CRC.